Retrenchment Strategies and Family Involvement: The Role of Survival Risk. (March 2019) - Casillas, Jose C.; Moreno-Menéndez, Ana M.; Barbero, José L.; Clinton, Eric
This article analyzes retrenchment strategies that family businesses adopt during periods of crisis. From a socioemotional wealth perspective, we propose that the influence of family board members and family CEOs on retrenchment depends on survival risk. We collected empirical data from companies on the Spanish Stock Exchange (2008-2012). Our findings reveal that family involvement intensifies retrenchment when performance is declining, and that retrenchment intensifies when survival is at risk. We also demonstrate that family firms are able to implement retrenchment measures when required to improve their performance.